Roll motion on small traditional Norwegian fishing vessels - Kristiansen, Gøran (UiT The Arctic University of Norway, 2021)
Roll motion is one of the six degrees of freedom and is the most difficult to predict, as roll motion is extremely sensitive to the viscous effect and induced flow separation. The smaller fishing vessel fleet commonly operates in almost all weather conditions, and sometimes in remote areas with cold arctic water where rescue can be far away and difficult. The safety of fishers depends on the vessel's characteristic to resist and maintain stability in high seas that can lead to large-amplitude motion with a combination of wave-induced ship motions. Roll motion can be a problem for vessels without any appendages that reduce the roll motion, e.g. bilge keels - stabilizers with no moving parts, form the most straightforward and cheapest element that can help decrease this motion. Through the last four decades, studies and investigation of roll motion use the approach developed by Ikeda et al. in the '70s and is the foundation to the guidelines presented by International Towing Tank Committee (ITTC). This thesis uses the procedures and guidelines from ITTC and compares the effects of bilge keel between model experiments and the numerical result.